Heart Rate Variability in Childhood Epilepsy - Karabulut, Muhammed; Yılmaz, Erdal; Serın, Hepsen Mine (My University, 2023)
Objective: Heart rate variability (HRV) is a non-invasive method used to assess the status of autonomic function of the heart. The aim of this prospective study was to assess HRV and cardiac function in children with epilepsy. In addition, the effects over HRV of epilepsy type, therapy regimens, refractory and well controlled epilepsy were investigated. Material and Method: Between September 2013 and March 2014, 61 epileptic children and 53 healthy children were included in the study. All subjects were evaluated by electrocardiography, echocardiography, and 24 hours rhythm holter. Results: In the children with epilepsy, it was determined a significant reduction in all the time domain (SDNN, SDNN index, SDANN, RMSSD, pNN50 p-values 0.011, 0.001, 0.021, 0.001, 0.001, respectively) and frequency domain (LF, HF, VLF p-values 0.001, 0.001, 0.001 respectively) parameters. There were not statistically significant differences in both time and frequency domain parameters between children with partial and generalized epilepsy. There was a significant reduction in SDNN, SDNN index, SDANN, RMSSD, LF, HF, VLF (p-values 0.009, 0.008, 0.015, 0.039, 0.004, 0.010, 0.005, respectively) values in the children who underwent polytherapy regimen. Conclusion: Epilepsy is associated with suppressed HRV values indicating decreased vagal activity. Having pathological EEG findings, and polytherapy regimen associated with refractory epilepsy are effective on suppressed HRV. In addition, cardiac systolic functions may be affected in patients with epilepsy under drug therapy. Keywords:
Keywords: Electrocardiography; Epilepsy; Heart Rate Variability